Polyamine based solid CO2 adsorbents for [11C]CO2 purification and radiosynthesis. (October 2022) - Chassé, Melissa; Sen, Raktim; Goeppert, Alain; Prakash, G.K. Surya; Vasdev, Neil
Abstract: Silica-grafted polyamines developed for CO2 capture are capable of reversibly and selectively capturing CO2 at ambient temperature. In this study, the feasibility of solid phase chemical adsorbents for purifying [ 11 C]CO2 from cyclotron target gas was investigated as an alternative to physical adsorption. Silica grafted polyethyleneimine (Si-g-PEI) demonstrated a high selectivity for [ 11 C]CO2 at room temperature with no detectable radiochemical impurities. Capture efficiencies from cyclotron target gas were 79 ± 12% for Si-g-PEI. Pure [ 11 C]CO2 was obtained in under 10 min via temperature-swing desorption. Si-g-PEI was easily regenerated with mild heating, though capture efficiencies decreased over multiple cycles. As a proof-of-concept, the positron emission tomography (PET) radiopharmaceutical [ 11 C]SL2511.88 was successfully synthesized from Si-g-PEI purified [ 11 C]CO2, providing molar activities on par with conventional methods. This work presents the first reusable, solid phase chemical adsorbents for capture and purification of [ 11 C]CO2 under mild conditions. Future work will focus on improved material longevity using materials with high thermal and oxidative stability. Graphical Abstract: ga1 Highlights: The first chemisorbent materials for purifying [ 11 C]CO2 was developed. Silica-grafted PEI selectively traps and releases [ 11 C]CO2 . Solid-phase trapping has potential for transporting isotopes of CO2 .